Putting proteomics on target: activity-based profiling of ubiquitin and ubiquitin-like processing enzymes. - Kessler, B (2006)
Modification of proteins with ubiquitin (Ub) and Ub-like modifiers (Ubls) plays a fundamental role in cell biology. As a consequence, proteomics-based efforts were developed to characterize proteins that are modified by Ub or Ubls. A more focused functional proteomics strategy relies on active-site probes based on the Ub/Ubl scaffold, which specifically targets Ub/Ubl-processing enzymes. Activity-based profiling with such tools led to the identification of novel gene products with Ub/Ubl-processing activity and uncovered novel control mechanisms regulating their activity. This review discusses recent advances in chemistry-based functional proteomics applications, and how this information can provide a framework for drug development against Ub/Ubl-processing enzymes.